The effect of hypoxia and reoxygenation on STAT3 regulation in potential cardiomyocyte models - Evans, Emma Louise (2012)
Cardiomyocyte apoptosis is an important contributory factor towards the progression of ischaemic heart disease. Signal Transducer and Activator of Transcription 3 (STAT3) is a transcription factor has that been implicated in normal heart development and function. Most interestingly, STAT3 also appears to play a role in cardioprotection, including hypoxic preconditioning. In this thesis the levels and activities of ST A T3 were measured in response to hypoxic insult in primary rat cardiomyocytes (RCMs) and two cardiomyocyte cell lines (H9c2 and P19CL6 cells). P19CL6 cells were extremely sensitive to hypoxia-induced apoptosis whereas RCMs and H9c2 cells were highly resistant.